Sans og samling: Om sammenligninger mellem musik og billede - Troelsen, Anders (K&K - Kultur og Klasse, 2019)
Mapping a span of extrinsic and intrinsic relationships between music and visual arts (including film), the article discusses ways of comparative analysis. It takes its starting point in concrete examples and proposes some provisional categories for this kind of aesthetic examination. Important for the comparative analysis is that it includes the specific sensory substance of the visual and auditory elements and sticks to a similar analytic level for both art forms. On the other hand, identifications of historical and structural convergence can assume an embarrassing concrete form without taking into account that often they should be located at a rather vague and overarching level. Acknowledging the necessity and usefulness of analogies, the article also warns against the obvious pitfalls involved.